CONSIDERATIONS FOR EVOLUTION OF INDOOR AND OUTDOOR EMISSION IN RELATION WITH THE PRINTING SPACE USING ECOLOGICAL RESIN FOR 3D DLP PRINTING - Mircea Dorin Vasilescu (Nonconventional Technologies Review, 2022)
The purpose of this paper is to identify whether it is important to use a filtration system for 3D priming solution with eco-friendly resin. The experimental program uses an ANYCUBIC printer and a set of sensors which was positioned in the box of the printer and other output of them. From the experimental tests performed at the level of the space in which the printing process is made, the change of the level of emission for formaldehyde is greater during the printing process than in the output areas considered. It can also be seen that for better control of the emission, it is recommended to use one or more filtration solution in the printing process.